Determinants of India's Manufactured Exports to South and North: A Gravity Model Analysis - Suresh K G; Neeraj Aswal (International Journal of Economics and Financial Issues, 2013)
We have analysed the determinants of India’s manufactured exports to its southern (developing countries) and northern (developed countries) markets. We employed an augmented gravity model to examine the determinants of India’s exports. The analysis shows that India’s exports to south and north is explained by the new trade theory variables like total GDP, GDP similarity and the difference in percapita income as an indicator of Heckschor-Ohlin theory of trade. However the distance is more negatively affecting India’s exports to north than the southern market as the proximity to southern market is helping India’s exports to grow in south.